2021
DOI: 10.1093/ibd/izab062
|View full text |Cite
|
Sign up to set email alerts
|

Residual Short-Segment Distal Inflammation Has No Significant Impact on the Major Relapse of Extensive Ulcerative Colitis

Abstract: Background Mucosal healing is a treatment target for patients with ulcerative colitis. However, the relevance of proactive treatment for residual inflammation limited to the distal colon is unclear. Materials and Methods Patients with ulcerative colitis who had extensive colitis in clinical remission and underwent colonoscopy were retrospectively enrolled and followed up for 2 years. Patients with complete endoscopic remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Clinical remission was assessed by the patient-reported outcome (PRO)-2 score, consisting of the rectal bleeding and stool sub-scores [ 23 ]. Clinical remission was defined as both “rectal bleeding sub-score = 0” and “stool sub-score ≤1” [ 24 ]. Patients with any following criterion were excluded: (1) proctitis, (2) after colectomy, (3) treated for UC other than thiopurine and/or 5-ASA (e.g., topical corticosteroids, systemic corticosteroids, tacrolimus, or Janus kinase inhibitors) within 1 month before the baseline, (4) under maintenance therapy with biologics, (5) past history of hematologic disorder, (6) pregnant woman, (7) after total gastrectomy, or (8) after ileocecal resection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical remission was assessed by the patient-reported outcome (PRO)-2 score, consisting of the rectal bleeding and stool sub-scores [ 23 ]. Clinical remission was defined as both “rectal bleeding sub-score = 0” and “stool sub-score ≤1” [ 24 ]. Patients with any following criterion were excluded: (1) proctitis, (2) after colectomy, (3) treated for UC other than thiopurine and/or 5-ASA (e.g., topical corticosteroids, systemic corticosteroids, tacrolimus, or Janus kinase inhibitors) within 1 month before the baseline, (4) under maintenance therapy with biologics, (5) past history of hematologic disorder, (6) pregnant woman, (7) after total gastrectomy, or (8) after ileocecal resection.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was the time to relapse, defined as the requirement of induction therapy for UC with the worsening of clinical symptoms [ 24 ]. The induction therapy included systemic corticosteroids, tacrolimus, cyclosporin A, leukocytapheresis, granulocyte and monocyte apheresis, biologic agents, Janus kinase inhibitor, indigo naturalis, any investigational new drug, or colectomy.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that fewer than two endoscopically active (MES > 0) distal segments (sigmoid and/or rectum) yield a similar risk of clinically significant relapse to complete mucosal healing (MES of 0), while more than three inflamed segments carry a higher risk. 3 Additionally, Shimodaira et al 4 reported that inflammation limited to less than 3 cm exhibited a comparable clinical outcome to complete mucosal healing. These findings made us believe in the importance of considering the extent of active disease regardless of MES of 1-3.…”
Section: Letter: Modifying the Mayo Endoscopic Subscore For Improved ...mentioning
confidence: 99%
“…4,5 One study reported that residual short-segment distal inflammation is not a risk factor for major relapses, provided that endoscopic remission is achieved in the proximal colon. 6 I would like to raise a few questions to the authors of this study. First, the severity of nonrectal inflammation and rectal inflammation was significantly different (p<0.001) between the groups and there was a wide variation in Ulcerative Colitis Segmental Endoscopic Index (UCSEI) scores.…”
Section: To the Editormentioning
confidence: 99%
“… 4 , 5 One study reported that residual short-segment distal inflammation is not a risk factor for major relapses, provided that endoscopic remission is achieved in the proximal colon. 6 …”
mentioning
confidence: 99%